An experimental investigation of a new perfect bond technology for composite slabs. (30th March 2018) - Ferrer, Miquel; Marimon, Frederic; Casafont, Miquel
Highlights: A new technology for bonding profiled steel sheeting and concrete is presented. Full-connection is achieved between steel and concrete until both materials yield. The longitudinal shear failure mode is extinguished in practice. The strength with the new system is much greater than with the embossments system. The new system provides high ductility to slabs through materials yielding. Abstract: Steel-concrete composite slabs generally fail due to the debonding with separation of sections caused by longitudinal shear forces, regardless of the shape of the sheeting profile or the design of the embossments. This article presents an innovative full-connection bonding technology, consisting of producing bands of many small crown-shaped cuttings in the profile webs as a replacement for the embossments. The new technology has been tested on three commercial sheeting profiles. The results of the investigation show that full connection is achieved with the new system, i.e., yielding of both materials occurs without any slip, in contrast to the partial connection of traditional embossments. The longitudinal shear strengths are 1.4–7 times higher. The specimens tested include the use of conventional galvanized steel and concrete, as well as ferritic stainless steel and lightweight aggregate concrete.